Range-dependent path-loss model in residential areas for the VHF and UHF bands. - Hyun Kyu Chung (IEEE Transactions on antennas and propagation)
Implementation digital fixed wireless systems, such as digital FM, high definition TV (HDTV) and wireless local loop (WILL), require a high level of accuracy of propagation prediction in the VHF and UHF bands. This paper presents a theoretical model that predicts the average path loss from an elevated base station to subscriber antennas at rooftop level in residential areas for frequencies in the approximate band from 30 MHz up to 3 GHz. In addition, the model gives the standard deviation of the path loss at the average rooftop level and the height gain for subscriber antennas above or below the average rooftop level. The approach used here generalizes that of Walfisch and Bertoni (1988), who developed a theoretical model of UHF propagation in urban environments. The rows of buildings in residential areas are modeled as a series of dielectric screens having random heights and uniform spacing. Propagation takes place over and through the dielectric screens, and ground reflections are included. The fields at the plane of each screen are obtained in terms of repeated numerical evaluation of the physical optics (PO) integral. Results obtained for the variation of the range dependence on frequency and row spacing are consistent with those previously found for high frequencies by assuming the screens to be totally absorbing. Using the results at different heights of receiving antenna allows computation of the height gain. The predictions are in agreement with the International Telecommunication Union Radio Communication (ITRU-R) recommendations in the VHF and UHF bands